Therapeutic monoclonal antibodies and clinical laboratory tests: When, why, and what is expected?. Issue 3 (15th August 2017) - Zhang, Zhanhu; Hu, Wenjie; Li, Linlin; Ding, Hongxia; Li, Haibo
Abstract : Background: We herein provide an overview of the clinical laboratory tests that should be performed before, during and after using therapeutic monoclonal antibodies (mAbs) and the clinical laboratory tests that may be affected by mAbs. Methods: The labels of FDA‐approved therapeutic mAbs were downloaded from DailyMed (the official website for drug labels) and were used as the sources of data for this review. Results: It was found that most of the labels provided information relevant to the clinical laboratory tests, including the tests needed before mAbs treatment to check the patients' background status and to identify potentially sensitive patients, the tests needed during or after the treatment to evaluate the patients' response, and the mAbs that may lead to false positive or negative results for clinical laboratory tests. Conclusions: The present findings will be of interest to physicians, laboratory scientists, those involved in drug development and surveillance and individuals making health care policy.